Rural community enterprises in Thailand: a case study of participation. (3rd April 2020) - Wongadisai, Worasit; Chanchalor, Sumalee; Murphy, Elizabeth
Community enterprises (CE) are a tool to support sustainable community development. They rely on community members' participation using a bottom-up, polycentric approach to management. However, they typically operate in rural areas where the required knowledge, management and marketing skills are often lacking. This study investigated members' participation in CEs and the failures and successes they encountered in participation in organisational, production, marketing and financial management. Data collection involved structured interviews with 400 participants in 200 CEs in north-eastern Thailand. The researchers also conducted focus groups with a successful CE (n = 5) and an unsuccessful CE (n = 7). Results revealed that participation was lowest for organisational, marketing and financial management. Lower levels of participation were associated with lack of time and lack of skill/education. Implications point to the value of outsourcing marketing and financial management for CEs in rural areas.